Records Appraisal in Network Organizations - Botticelli, Peter (Archivaria, 2000)
This article explores the need for new approaches to the appraisal of records in so-called network organizations, which emphasize informal, collaborative work processes. More and more records, increasingly in digital form, are created as part of unstructured or less-structured processes; archivists will have to appraise both the records and the administrative processes whereby such records are created. Also, as archivists confront a rapidly changing workplace and an increasingly diverse body of records, it may be necessary to broaden the traditional concept of provenance to account for the impact of new information technologies and organizational forms on the social meaning of records and record types. This article, buttressed by a case study, presents one possible framework for the appraisal of records which are part of thei nfrastructure, or which serve as tools for accomplishing tasks, in a collaborative work environment. RÉSUMÉ Cet article explore le besoin de nouvelles approches de tri des documents ausein des organisations fonctionnant en réseau, lesquelles mettent l’emphase sur desprocessus informels de travail et de collaboration. De plus en plus de documents, et cela en nombre croissant sous forme informatique, sont créés dans le cadre de ces processus plus ou moins structurés. Les archivistes devront évaluer ces documents et les processus administratifs dans le cadre desquels ils sont créés. De plus, comme les archivistes sont confrontés à un changement rapide du monde du travail et à une plus grande panoplie de documents, il serait peut-être nécessaire d’élargir le concept traditionnel de provenance dans le but de tenir compte des effets des nouvelles technologieset des formes d’organisations sur la signification sociale des documents et de leurs différents types. L’article, étayé par une étude de cas, présente un cadre possible pour l’évaluation des documents faisant partie de l’infrastructure, ou qui servent d’outils à la réalisation des tâches, dans un environnement de travail basé sur la collaboration.